Geoff Cloke at 65: a pioneer in organometallic chemistry. Issue 30 (13th July 2018) - Arnold, Polly L.; Green, Jennifer C.; Green, Malcolm L. H.; Kilpatrick, Alexander F. R.; Layfield, Richard A.; Love, Jason B.; O'Hare, Dermot; Turner, John F. C.
Abstract : We are delighted to present this collection of articles to celebrate the work of Geoff Cloke on the occasion of his 65th birthday. Abstract : Professor Geoff Cloke FRS celebrates his 65 th birthday in 2018. In a career spanning four decades, his research endeavours have accounted for some of the most innovative synthetic chemistry of the modern era, with his many publications describing truly exceptional compounds and experimental methods that portray a unique chemical imagination. In addition to his scientific accomplishments, Cloke can be particularly proud of his successful mentoring, a level of dedication that propelled many students and post-docs on to become research leaders in their own right. In compiling this collection of some of his research articles, a small cross-section of his friends, colleagues and collaborators, wish to pay tribute to his modesty, compassion and generous personality.